Semester-Long Assessment of Aseptic Technique in Microbiology Labs - Daniel Aruscavage (American Society for Microbiology, 2013)
Biology educators emphasize aseptic technique when teaching lab courses. Aseptic technique is very important in microbiology to ensure safety and prevent cross-contamination. Although it can be assessed throughout the semester by examining the students’ technique and observation of contamination, this tool offers a simple semester-long graded assessment of each student’s technique. The procedures allow the students to perform a quick exercise that can determine if cross-contamination occurs, thus determining if aseptic technique was observed. Instructors can quickly check for the presence of cross-contamination. After implementing this procedure, a quantifiable improvement in my students’ aseptic technique throughout the semester was observed. It was noted that between the middle and end of the semester there was a slight increase in the amount of cross-contamination but still well below the contamination observed at the beginning of the semester. This procedure was a valuable way to assess aseptic technique during the course of a semester. A search for “aseptic technique” on the American Society of Microbiology website reveals that several lab experiments and job opportunities mention the importance of aseptic technique. It is a skill that must be used for all laboratory procedures when working with microorganisms. It is important for both the safety of the students and for the proper handling of microorganisms. There are several good explanations of aseptic technique on the Internet, and the Nuffield Foundation provides a very good description of techniques (1). The goal of this project is to provide instructors with a tool to assess the aseptic technique of their students by using simple transfers of bacteria to fresh media to identify cross-contamination. When class experiments do not work students may not understand how poor aseptic technique impacted the project. This tool would work best for undergraduate students in an introductory microbiology course, so students can see the effects of poor aseptic technique. Adding a graded assignment to their aseptic technique ensures their full effort in this key aspect of microbiology. The procedure can be presented during the first laboratory meeting as a way to explain the importance of aseptic technique and transferring cultures. It works well as an introductory lab since it also introduces the students to microorganisms and the need to incubate samples to observe growth. This semester I used this tool as a way to monitor the students’ progress from the beginning to the end of the semester. I made it a part of their first class, the midterm practical, and their final practical.